Etude de la Qualité de Vie des Laryngectomisés Partielles et des Laryngectomisés Totales en Utilisant L’echelle Fact H-N - Boubechtoula, Saliha (جامعة قاصدي مرباح - ورقلة, 2022)
The current study aims to diagnose the partial and total laryngetomized quality of life in Algerian hospital environment trough other dimension such as personel emotional social, family and professionnal. the study sample consists of 29 cases of total laryngectomized , 15 men and 5 women, and 9 cas of partial laryngectomized, The study results show that partical laryngectomized quality of life in personal, emotional and professional is low compared with family side however the professional and emotional side of total laryngectomized is low and personal one is average and the family side is high . Regarding the gender ,the quality of life is equal as in laryngectomy type ,education, quality variable and in other proffession.
Keywords: الصحة النفسية -- جودة الحياة -- استئصال الحنجرة